PERANAN MODAL SOSIAL PADA KELOMPOK TANI PADI SAWAH DI DESA TAWAANG KECAMATAN TENGA KABUPATEN MINAHASA SELATAN - Jimmy ., Rumagit; Jean Fanny Junita Timban; Charles Reijnaldo Ngangi (Sam Ratulangi University, 2019)
The purpose of this study was to determine and describe the role of social capital, consisted by trust, social norms, social networks, in the paddy rice farmer group in Tawaang Village, Tenga Sub-district, South Minahasa Regency. This research lasted for three months from July to September 2019. The data used in this study were primary data obtained from direct interviews and observations. Interviews were conducted with the help of a questionnaire. The Head of Village and farmer group members represent the community. Total respondents were 12 people who were all members of the group. Secondary data were obtained from the Tawaang Village Office, local bookstores and via the internet. Internet through Google Scholar to get articles from various scientific journals and theses from other universities related to research on the Role of Social Capital in Paddy Farmer Groups. The results showed that the index figure of 81.48% meant that it was classified in the existing category. Thus, the role of social capital was properly realized in the Tunas Harapan Farmer Group in Tawaang Village, Tenga District, South Minahasa Regency in the form of trust, social norms and social networks. Group members lead a high social life both within the group and outside the group, namely to strengthen the kinship, tolerance and efforts so that the farming business that runs well.*eprm*Â